A Study on the Negative Slope Mechanism of the Friction Torque Based on Viscoelastic Side Contact Model of Asperity - Li Jie; Chen Cheng; Wang Zhiyong (Jixie chuandong)
Taking the friction pair of wet brake as the research object, based on the micro surface contact theory and considering the influence of viscous forces between the asperity, the asperity side-contact viscoelastic model of the asperity friction surface is established. By normalizing and integrating the microscopic model, the formulae for the relationship between the macroscopic axial pressure, rotational speed and frictional torque, which reflect the characteristics of the microscopic model parameters, are derived, and the microscopic mechanism of the negative slope of the frictional torque-speed characteristic at low rotational speeds is obtained. The results show that when the axial pressure and the asperity dimensionless radius of curvature are reduced, the minimum value of the frictional torque variation rate (dTf /dn) will increase and the amount of the frictional torque variation will decrease, which is beneficial to reduce the wear of friction pairs. At the same time, through the bench experiment, the relationship between the negative slope characteristics and related parameters is reproduced. Compared with the experimental test, the accuracy of the theoretical analysis model is 86.82%, and the simulation results are accurate. This is of important theoretical significance for further studying the friction performance and improving the service life of friction pairs.